Preparation method of high-rate low-temperature-resistant lithium ion battery negative electrode material
By heating artificial graphite, niobium chlorine and zirconium chlorine in an oxidation atmosphere, forming a composite material, the shortcomings of the negative electrode materials of lithium-ion batteries in terms of ratio and low temperature resistance are solved, and the charging and discharging performance and low temperature of the battery are significantly improved. Adaptability.
Patent Information
- Application Number
- CN202411497076.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing lithium-ion battery anode materials have shortcomings in terms of rate performance and low-temperature resistance, and cannot meet the requirements of fast charging and low-temperature environments of new energy vehicles.
By mixing artificial graphite, niobium chlorine and zirconium chlorine in a specific proportion, and heating in an oxidative atmosphere, the alkyl group on its surface is converted into hydroxyl and carboxy groups, combining niobium hydroxide and zirconium hydroxide to form high electron conductivity and high Composite materials with ionic conductivity, mechanical strength and electrochemical properties of reinforced materials.
It significantly improves the rate performance and low temperature performance of lithium-ion batteries, improves the mechanical strength and electrochemical performance of materials, and meets the use requirements of new energy vehicles.
Smart Images

Figure CN119240790A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a negative electrode material for a high-rate, low-temperature-resistant lithium ion battery. Background technology:
[0002] The power source of new energy vehicles is mainly lithium-ion batteries. Their rapid development and large-scale application have led to higher and higher requirements for the charging speed (measured by rate performance) and low-temperature operating environment of lithium-ion batteries. As an important component of lithium-ion batteries, the rate performance and low-temperature resistance of negative electrode materials have a significant impact on the charging speed and low-temperature environment performance of lithium-ion batteries, and the low-temperature resistance is positively correlated with the rate performance.
[0003] The current commercial lithium-ion battery negative electrode is mainly based on artificial graphite, but its rate performance and low temperature resistance are limited and can no longer meet the requirements of new energy vehicles. Since the current commercial lithium-ion battery negative electrode material preparation process and related technologies are already very stable and mature, there is basically no room for improvement in its rate performance and low temperature resistance, which seriously restricts the market promotion of new energy vehicles. Summary of the invention:
[0004] In order to solve the above problems, the first object of the present invention is to provide a method for preparing a high-rate, low-temperature resistant lithium-ion battery negative electrode material, the second object of the present invention is to provide a high-rate, low-temperature resistant lithium-ion battery negative electrode material, and the third object of the present invention is to provide an application of a high-rate, low-temperature resistant lithium-ion battery negative electrode material.
[0005] The first object of the present invention is implemented by the following technical solutions:
[0006] A method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material comprises the following steps:
[0007] S1. Weigh artificial graphite, niobium oxychloride and zirconium oxychloride in proportion, mix and stir evenly to obtain a mixture A;
[0008] S2, adding deionized water to the mixture A obtained in step S1 to dissolve the niobium oxychloride and zirconium oxychloride in the mixture A to obtain a solid-liquid coexisting mixture B;
[0009] S3, adding a precipitant to the mixture B obtained in step S2 to convert the niobium ions and zirconium ions in the mixture B into niobium hydroxide and zirconium hydroxide, respectively, to obtain a reaction product;
[0010] S4, filtering, washing, and drying the reaction product obtained in step S3 to obtain a solid mixture C of artificial graphite-niobium hydroxide-zirconium hydroxide;
[0011] S5. The solid mixture C obtained in step S4 is heated in an oxidizing atmosphere to convert the alkyl groups on the surface of the artificial graphite into acidic groups such as hydroxyl groups and carboxyl groups, which are then combined with the decomposition products of niobium hydroxide and zirconium hydroxide and ball-milled to obtain a high-rate, low-temperature-resistant lithium-ion battery negative electrode material.
[0012] Furthermore, in step S1, the mass ratio of artificial graphite, niobium oxychloride and zirconium oxychloride is 100:1.62-2.43:5.2-7.9.
[0013] Furthermore, in step S2, the mass ratio of mixture A to deionized water is 1:2.5-4.
[0014] Furthermore, in step S3, the precipitant is ammonia water, and the added volume (ml) of ammonia water ranges from the sum of 1.8 times the mass (g) of zirconium oxychloride and 3.3 times the mass (g) of niobium oxychloride to the sum of 2.0 times the mass (g) of zirconium oxychloride and 3.5 times the mass (g) of niobium oxychloride.
[0015] Furthermore, the washing in step S4 is performed in a tripod centrifuge with a centrifugal frequency of 50 Hz.
[0016] Furthermore, the drying in step S4 is carried out in a freeze dryer with a vacuum pressure of 60 to 100 Pa, a drying temperature of -20 to -40°C, and a drying time of 2 to 4 hours.
[0017] Furthermore, the heating reaction in step S5 is carried out in a tubular furnace, the reaction atmosphere is oxygen, the oxygen flow rate is 100-200 ml / min, the heating temperature is 400-600° C., the heating rate is 3-6° C. / min, and the reaction time is 1-3 hours.
[0018] The second object of the present invention is implemented by the following technical solutions:
[0019] A method for preparing a high-rate and low-temperature-resistant lithium-ion battery negative electrode material obtains a high-rate and low-temperature-resistant lithium-ion battery negative electrode material.
[0020] The third object of the present invention is implemented by the following technical solutions:
[0021] The invention discloses an application of a high-rate and low-temperature-resistant lithium-ion battery negative electrode material in the preparation of lithium-ion batteries.
[0022] Advantages of the present invention:
[0023] 1. Compound artificial graphite with niobium oxide and zirconium oxide, and use the high electronic conductivity of niobium oxide and the high ionic conductivity of zirconium oxide to accelerate the lithium ion transmission rate and electron movement rate of artificial graphite as the negative electrode of lithium-ion battery during the charge and discharge process, thereby improving its charge and discharge rate performance and further improving its low temperature resistance;
[0024] 2. First, a certain proportion of crystal water in niobium hydroxide and zirconium hydroxide is removed by low-temperature drying under vacuum conditions, and then the artificial graphite is heated and oxidized under medium temperature conditions in an oxidizing atmosphere so that the alkyl groups on the surface are converted into acidic groups such as hydroxyl and carboxyl groups, and then combined with niobium hydroxide and zirconium hydroxide in the form of covalent bonds and hydrogen bonds. The two chemical bonds have high bond energies, which enhance the bonding force between artificial graphite and niobium hydroxide and zirconium hydroxide, thereby making the composite material have higher mechanical strength. Description of the drawings:
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 It is a comparison chart of the rate performance and low temperature performance test results of Example 2. Specific implementation method:
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1:
[0029] A method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material comprises the following steps:
[0030] S1, adding 1000g of artificial graphite, 18g of niobium oxychloride and 60g of zirconium oxychloride into a reaction kettle and stirring evenly to obtain a mixture A;
[0031] S2, adding 3000 g of deionized water to the mixture A obtained in step S1 to dissolve the niobium oxychloride and zirconium oxychloride in the mixture A to obtain a solid-liquid coexisting mixture B;
[0032] S3, adding 173 ml of 25% ammonia water at a rate of 3 ml / min to the mixture B obtained in step S2, so that the niobium ions and zirconium ions in the mixture B are converted into niobium hydroxide and zirconium hydroxide, respectively, to obtain a reaction product;
[0033] S4, filtering the reaction product obtained in step S3, centrifuging in a tripod centrifuge at a centrifugal frequency of 50 Hz for 10 minutes to separate the solid and liquid, then adding 5 L of deionized water for centrifugal washing for 5 minutes, repeating the operation of adding deionized water and centrifugal washing until the pH value of the wastewater discharged after centrifugal washing is less than 7;
[0034] Then, the centrifuged material was transferred to a freeze dryer, vacuumed to 80 Pa, the vacuum drying temperature was set to -30°C, and dried for 3 hours to obtain a solid mixture C of artificial graphite-niobium hydroxide-zirconium hydroxide;
[0035] S5. The solid mixture C obtained in step S4 is placed in a tubular furnace, and heated for 1.5 hours under the conditions of an oxygen flow rate of 150 ml / min, a heating temperature of 450° C., and a heating rate of 3° C. / min, so that the alkyl groups on the surface of the artificial graphite are converted into acidic groups such as hydroxyl groups and carboxyl groups, which are then combined with the decomposition products of niobium hydroxide and zirconium hydroxide, and then ball-milled and mixed in a vertical planetary ball mill at a ball-milling speed of 300 r / min for 1.5 hours, thereby obtaining a high-rate, low-temperature-resistant lithium-ion battery negative electrode material.
[0036] In this embodiment, the precipitant ammonia water is a liquid (solution), and the precipitant reacts with niobium oxychloride and zirconium oxychloride to generate niobium hydroxide and zirconium hydroxide precipitates. The role of filtering in step S4 is to separate the zirconium hydroxide and niobium hydroxide precipitates, graphite and liquid precipitants into solid and liquid, thereby obtaining a composite material precursor of zirconium hydroxide, niobium hydroxide and graphite. After drying, zirconium hydroxide and niobium hydroxide also exist in a solid form in combination with graphite, and before drying, they exist in a solid-liquid mixed state (colloid). The role of washing is to clean the precipitant with deionized water, and the role of drying is to dry the residual deionized water after washing. In step S5, the role of heating is actually to oxidize the alkyl groups on the surface of artificial graphite into hydroxyl groups (-OH) and carboxyl groups (-COOH) in the presence of oxygen, and to better combine with the decomposition products of niobium hydroxide and zirconium hydroxide (niobium oxide and zirconium oxide with hydroxyl groups on the surface) later. The decomposition products of niobium hydroxide and zirconium hydroxide are niobium oxide and zirconium oxide with hydroxyl groups on the surface. Niobium oxide is a material with strong electronic conductivity, and zirconium oxide is a material with strong lithium ion conductivity. When combined with the graphite negative electrode, it can enhance the electron and lithium ion conductivity of the lithium-ion battery, thereby improving the charge and discharge performance, that is, the rate performance. The raw material for the preparation of artificial graphite is petroleum coke. The main components of petroleum coke are C, H, and O. Therefore, after the artificial graphite is prepared, some alkyl groups (-CH3) will remain on the surface of the graphite. The reaction formula corresponding to the above process is:
[0037] -CH3+O2=CH2OH;
[0038] -CH3+O2=COOH+H2O
[0039] Embodiment 2:
[0040] A method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material comprises the following steps:
[0041] S1, adding 1000g of artificial graphite, 20g of niobium oxychloride and 68g of zirconium oxychloride into a reaction kettle and stirring evenly to obtain a mixture A;
[0042] S2, adding 3500 g of deionized water to the mixture A obtained in step S1 to dissolve the niobium oxychloride and zirconium oxychloride in the mixture A to obtain a solid-liquid coexisting mixture B;
[0043] S3, adding 193 ml of 25% ammonia water at a rate of 3 ml / min to the mixture B obtained in step S2, so that the niobium ions and zirconium ions in the mixture B are converted into niobium hydroxide and zirconium hydroxide, respectively, to obtain a reaction product;
[0044] S4, filtering the reaction product obtained in step S3, centrifuging in a tripod centrifuge at a centrifugal frequency of 50 Hz for 10 minutes to separate the solid and liquid, then adding 5 L of deionized water for centrifugal washing for 8 minutes, repeating the operation of adding deionized water and centrifugal washing until the pH value of the wastewater discharged after centrifugal washing is less than 7;
[0045] Then, the centrifuged material was transferred to a freeze dryer, vacuumed to 60 Pa, the vacuum drying temperature was set to -40°C, and dried for 3.5 hours to obtain a solid mixture C of artificial graphite-niobium hydroxide-zirconium hydroxide;
[0046] S5. The solid mixture C obtained in step S4 is placed in a tubular furnace, and heated for 5 hours under the conditions of an oxygen flow rate of 180 ml / min, a heating temperature of 500° C., and a heating rate of 4° C. / min, so that the alkyl groups on the surface of the artificial graphite are converted into acidic groups such as hydroxyl groups and carboxyl groups, and then combined with the decomposition products of niobium hydroxide and zirconium hydroxide, and then ball-milled and mixed in a vertical planetary ball mill at a ball-milling speed of 300 r / min and a ball-milling time of 1.5 hours, thereby obtaining a high-rate and low-temperature-resistant lithium-ion battery negative electrode material.
[0047] Comparative Example 1:
[0048] In this comparative example, artificial graphite is used as the negative electrode material.
[0049] The negative electrode materials of Example 1, Example 2 and Comparative Example 1 were tested for rate performance and low temperature performance, and the test results are shown in Table 1 and Table 2, respectively. The battery assembly preparation process is: using metallic lithium as the negative electrode active material, the high-rate, low-temperature resistant lithium-ion battery negative electrode materials prepared in Example 1 and Example 2 and the negative electrode material of Comparative Example 1 are used as positive electrode active materials, assembled into CR2430 button half-cells, and the rate performance and low temperature performance tests are carried out according to the following charge and discharge procedures and test methods. The test adopts the CT2001A blue electric test system.
[0050] 1. Rate performance test process. 1. Stand at room temperature for 4 hours; 2. 0.1C discharge, cut-off voltage 0.005V; 3. 0.05C discharge, cut-off voltage 0.005V; 4. Stand for 5 minutes; 5. 0.1C charge, cut-off voltage is 2.0V; 6. 1C discharge, cut-off voltage 0.005V, 0.9C discharge, cut-off voltage 0.005V, 0.8C discharge, cut-off voltage 0.005V, 0.7C discharge, cut-off voltage 0.005V, 0. 6C discharge, cut-off voltage 0.005V, 0.5C discharge, cut-off voltage 0.005V, 0.4C discharge, cut-off voltage 0.005V, 0.3C discharge, cut-off voltage 0.005V, 0.2C discharge, cut-off voltage 0.005V, 0.1C discharge, cut-off voltage 0.005V; 7. 1C charge, cut-off voltage 2V; 8. Record the percentage ratio of 1C charging gram capacity to 0.1C charging gram capacity, which is the rate performance.
[0051] 2. Low temperature performance test process. 1. Stand at room temperature for 4 hours; 2. 0.1C discharge, cut-off voltage 0.005V; 3. 0.05C discharge, cut-off voltage 0.005V; 4. 0.1C charge, cut-off voltage is 2.0V; 5. Stand for 5 minutes; 6. 0.1C discharge, cut-off voltage 0.005V; 7. 0.05C discharge, cut-off voltage 0.005V; 8. Stand in a -20℃ freeze drying oven for 24 hours; 6. 5. 0.1C charge, cut-off voltage is 2.0V; 7. Record the percentage of the charged gram capacity after being placed at -20℃ for 24 hours and the charged gram capacity after being placed at room temperature for 4 hours, which is the low temperature performance.
[0052] Table 1 Rate performance test results
[0053]
[0054]
[0055] Table 2 Low temperature performance test results
[0056]
[0057] The test results of Table 1 and Table 2 are Figure 1 It can be intuitively seen that the present invention can effectively improve the rate performance and low temperature performance of lithium-ion batteries, and the improvement effect of low temperature performance is particularly significant.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material, characterized in that: The following steps are involved: S1. Weigh artificial graphite, niobium oxychloride and zirconium oxychloride in proportion, mix and stir evenly to obtain a mixture A; S2, adding deionized water to the mixture A obtained in step S1 to dissolve the niobium oxychloride and zirconium oxychloride in the mixture A to obtain a solid-liquid coexisting mixture B; S3, adding a precipitant to the mixture B obtained in step S2 to convert the niobium ions and zirconium ions in the mixture B into niobium hydroxide and zirconium hydroxide, respectively, to obtain a reaction product; S4, filtering, washing, and drying the reaction product obtained in step S3 to obtain a solid mixture C of artificial graphite-niobium hydroxide-zirconium hydroxide; S5. The solid mixture C obtained in step S4 is heated in an oxidizing atmosphere to convert the alkyl groups on the surface of the artificial graphite into acidic groups such as hydroxyl groups and carboxyl groups, which are then combined with the decomposition products of niobium hydroxide and zirconium hydroxide and ball-milled to obtain a high-rate, low-temperature-resistant lithium-ion battery negative electrode material.
2. The method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material according to claim 1, characterized in that: In the step S1, the mass ratio of artificial graphite, niobium oxychloride and zirconium oxychloride is 100:1.62-2.43:5.2-7.
9.
3. The method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material according to claim 1, characterized in that: In the step S2, the mass ratio of the mixture A to the deionized water is 1:2.5-4.
4. The method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material according to claim 1, characterized in that: In step S3, the precipitant is aqueous ammonia.
5. The method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material according to claim 1, characterized in that: The washing in step S4 is performed in a tripod centrifuge at a centrifugal frequency of 50 Hz.
6. The method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material according to claim 1, characterized in that: The drying in step S4 is carried out in a freeze dryer with a vacuum pressure of 60 to 100 Pa, a drying temperature of -20 to -40°C, and a drying time of 2 to 4 hours.
7. The method for preparing a high-rate low-temperature-resistant lithium-ion battery negative electrode material according to claim 4, characterized in that: The heating reaction in step S5 is carried out in a tubular furnace, the reaction atmosphere is oxygen, the oxygen flow rate is 100-200 ml / min, the heating temperature is 400-600° C., the heating rate is 3-6° C. / min, and the reaction time is 1-3 hours.
8. A high-rate, low-temperature-resistant lithium-ion battery negative electrode material prepared by the method for preparing a high-rate, low-temperature-resistant lithium-ion battery negative electrode material according to any one of claims 1 to 7.
9. Use of the high-rate, low-temperature-resistant lithium-ion battery negative electrode material according to claim 8 in the preparation of lithium-ion batteries.
